1984
DOI: 10.1515/znc-1984-11-1236
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Field Evaluation of a Sex Pheromone of the European Pine Moth

Abstract: Forstliche Versuchs-und Forschungsanstalt B a d en -W ü rt tem berg, D-7801 Stegen-W ittental Sex Pherom one, (Z ,£ )-5 ,7 -D o d ec ad ie n al, P h ero m o n e In hibitors, Olfactory Receptors, D endrolim us pini, L asiocam pidae The principal com ponent o f the fem ale sex p h e ro m o n e of the E uropean pine m oth Dendrolimus p in i L. (L asiocam pidae) was identified as (Z ,E )-5 ,7 -dodecadienal by capillary gas chrom atography, m ass spectrom etry, single receptor analyses, and field trap p in g tests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 3 publications
0
19
1
Order By: Relevance
“…Furthermore, the minor components, Z5-12: OAc and (5Z,7E)-5,7-dodecadien-1-yl propionate, function to enhance the specificity of the signals, respectively. In addition, Z5,E7-12:OAc is known to serve as a strong inhibitor of European pine caterpillar moth D. pini whose major pheromone component is Z5,E7-12:Ald (Priesner et al, 1984). In the current research, Z5,E7-12:Ald at relatively high dose showed strong antagonistic effects on attraction of male D. kikuchii, although trace quantities of it have been found in the gland extracts.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Furthermore, the minor components, Z5-12: OAc and (5Z,7E)-5,7-dodecadien-1-yl propionate, function to enhance the specificity of the signals, respectively. In addition, Z5,E7-12:OAc is known to serve as a strong inhibitor of European pine caterpillar moth D. pini whose major pheromone component is Z5,E7-12:Ald (Priesner et al, 1984). In the current research, Z5,E7-12:Ald at relatively high dose showed strong antagonistic effects on attraction of male D. kikuchii, although trace quantities of it have been found in the gland extracts.…”
Section: Discussionmentioning
confidence: 46%
“…So far, sex pheromones have been reported for the masson pine caterpillar moth, D. punctatus (Zhao et al, 1993), the pine moth, D. spectabilis (Ando et al, 1982;Kong et al, 2003), the larch caterpillar moth, D. superans (Klun et al, 2000;Kong et al, 2007a), the Yunnan pine caterpillar moth, D. houi (Kong et al, 2007b), and the European pine moth D. pini (Priesner et al, 1984;Kovalev et al, 1993). Sex pheromones components that have been identified from Dendrolimus species are all (5Z,7E)-5,7-dodecadienes with different terminal functional groups (alcohol, acetate, propionate, and aldehyde), except for the sex pheromone of D. houi, which was reported as a mixture of (5E,7Z)-5,7-dodecadien-1-yl acetate (E5,Z7-12:OAc), (5E,7Z)-5,7-dodecadien-1-ol (E5,Z7-12:OH), and (5E,7Z)-5,7-dodecadienal (E5,Z7-12:Ald) (Kong et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Z5,E7-12:Ald is a major pheromone component of a closely related species, D. pini (Prisner et al, 1984) and a likely inhibitor of the attractant pheromone blend in D. punctatus (Zhao, unpublished data). It may be hypothesized that decapitated females or gland incubations lose a factor or mechanism to control the specific pheromone blend produced by normal females.…”
Section: Discussionmentioning
confidence: 99%
“…All baits containing Z5,E7-12:Ald with or without other gland components trapped more male D. superans than controls. In D. pini, E5,Z7-12:Ald is a powerful antagonist to its sex pheromone, Z5,E7-12:Ald (Priesner et al, 1984). In D. pini, E5,Z7-12:Ald is a powerful antagonist to its sex pheromone, Z5,E7-12:Ald (Priesner et al, 1984).…”
Section: Field Trialsmentioning
confidence: 99%
“…The sex pheromone of Dendrolimus punctatus consists of ( Z,E )-5,7-dodecadienol ( Z 5, E 7-12:OH), ( Z,E )-5,7-dodecadienyl acetate ( Z 5, E 7-12:OAc), ( Z,E )-5,7-dodecadienyl propionate ( Z 5, E 7-12:OPr), ( Z )-5-dodecenol ( Z 5-12:OH), and ( Z )-5-dodecenyl acetate ( Z 5-12:OAc) in a ratio of 7.9:6.5:2.4:2.6:1.0 (Zhao et al, 1993), whereas the sex pheromones of Dendrolimus spectabilis and Dendrolimus pini consist of Z 5, E 7-12:OH (Ando et al, 1982) and ( Z,E )-5,7-dodecadienal ( Z 5, E 7-12:Ald), respectively (Priesner et al, 1984). The sex pheromone of Dendrolimus punctatus consists of ( Z,E )-5,7-dodecadienol ( Z 5, E 7-12:OH), ( Z,E )-5,7-dodecadienyl acetate ( Z 5, E 7-12:OAc), ( Z,E )-5,7-dodecadienyl propionate ( Z 5, E 7-12:OPr), ( Z )-5-dodecenol ( Z 5-12:OH), and ( Z )-5-dodecenyl acetate ( Z 5-12:OAc) in a ratio of 7.9:6.5:2.4:2.6:1.0 (Zhao et al, 1993), whereas the sex pheromones of Dendrolimus spectabilis and Dendrolimus pini consist of Z 5, E 7-12:OH (Ando et al, 1982) and ( Z,E )-5,7-dodecadienal ( Z 5, E 7-12:Ald), respectively (Priesner et al, 1984).…”
Section: Introductionmentioning
confidence: 99%